Era Amatir Sepakbola Jepang dan Pengaruh Konsep Shokuba Supotsu (職場スポーツ) (1965-1992) - Robbani, Muhammad; Ong, Susy (Vocational College of Diponegoro University, 2024)
Abstract This article reviews the long amateur era of Japanese football which was heavily influenced by the concept of Shokuba Supotsu (workplace sport/職場スポーツ). The amateur era of Japanese football arguably began in 1921, as marked by the birth of the Emperor's Cup tournament. Later, there was also Japan Soccer League (日本サッカーリーグ, Nihon Sakkā Rīgu/JSL), an amateur competition held from 1965 to 1992. At first, the Emperor's Cup was dominated by teams from educational institutions. Then started to change from 1963, with the presence of corporate clubs in the Emperor's Cup. Since then, corporate clubs have begun to dominate Japanese football competitions. However, these corporate clubs are run amateurishly because they do not apply aspects of professional football. Players (who are also employees of their team's corporation) must divide their time between working for their company and playing in football competitions. So corporate players do not focus on carrying out their activities as footballers. The Japanese football amateur era stopped in 1992 when the JSL competition changed to J. League in 1993. Only professional clubs could participate in J. League, so amateur corporate football clubs didn’t have a reason to exist anymore since they should transform into professional clubs. This paper uses a literature study method from previous studies with similar themes. Before becoming an Asian football powerhouse like today, Japanese football had difficulty to develop because football was run in an amateur way.